THE PROBLEM OF RESPONSIBILITY OF THE AIR TRAFFIC CONTROLLER -TRAINEE IN ASPECT OF APPLICATION OF ART 263 OF THE CRIMINAL CODE OF RUSSIAN FEDERATION - S. S. Yurev (Научный вестник МГТУ ГА, 2016)
In this article the legal status of the air traffic controller-trainee in aspect of responsibility for violation of safety rules of flights is developed. The conclusion is drawn that he can bear responsibility only in case he worked contrary to instructions, obligatory for him, or without coordination with the air traffic controller-instructor.